Chitin, Chitosan, and Glycated Chitosan Regulate Immune Responses: The Novel Adjuvants for Cancer Vaccine - Xiaosong Li; Min Min; Nan Du; Ying Gu; Tomas Hode; Mark Naylor; Dianjun Chen; Robert E. Nordquist; Wei R. Chen (Clinical and Developmental Immunology)
With the development of cancer immunotherapy, cancer vaccine has become a novel modality for cancer treatment, and the important role of adjuvant has been realized recently. Chitin, chitosan, and their derivatives have shown their advantages as adjuvants for cancer vaccine. In this paper, the adjuvant properties of chitin and chitosan were discussed, and some detailed information about glycated chitosan and chitosan nanoparticles was also presented to illustrate the trend for future development.